Elsewhere [compact disc, unabridged] - Koontz, Dean R. (Dean Ray), 1945- (Brilliance Audio, Inc., 2020)
Since his wife, Michelle, left seven years ago, Jeffy Coltrane has worked to maintain a normal life for himself and his eleven-year-old daughter, Amity, in Suavidad Beach. It's a quiet life, until a local eccentric known as Spooky Ed shows up on their doorstep. Ed entrusts Jeffy with hiding a strange and dangerous object, something he calls "the key to everything', and tells Jeffy that he must never use the device. But after a visit from a group of ominous men, Jeffy and Amity find themselves accidentally activating the key and discovering an extraordinary truth.